Analisis Semiotika Ferdinand de Saussure pada Lagu “Paralel” Karya Febian Winanda - Putri, Shintya; Setyanto, Yugih (Kiwari, 2025)
Music is an art form with extraordinary power in conveying emotions and messages. Lyrics function as a medium of expression in music, through which songwriters employ creativity and linguistic play to create distinctive meanings and aesthetic appeal. The song “Paralel” by Febian Winanda demonstrates strong artistic and symbolic qualities, making it a compelling subject for academic analysis, particularly through a semiotic approach. This study aims to identify and interpret the meanings and messages embedded in the lyrics of “Paralel” as received by listeners. The research draws upon Reception Theory and popular culture theory as its theoretical framework. A qualitative research method is employed, utilizing Ferdinand de Saussure’s semiotic analysis to examine the relationship between signs and meanings in the song lyrics. The findings reveal that most listeners occupy a dominant position, in which they accept the song’s message in accordance with the songwriter’s intended meaning. However, some listeners adopt a negotiated position, interpreting the lyrics by adapting the meaning to their personal experiences. Furthermore, each word and phrase in the song is understood not only at a literal level but also as a signifier that refers to deeper emotional and symbolic meanings (signifieds), such as hope, distance, and unrequited love. The relationship between sign and meaning is shown to be arbitrary and contextual, shaped by the listener’s social background and lived experiences. Musik merupakan salah satu bentuk seni yang memiliki kekuatan luar biasa dalam menyampaikan emosi dan pesan. Lirik berfungsi sebagai medium ekspresi dalam musik, di mana pencipta lagu memanfaatkan kreativitasnya dalam memainkan kata-kata sehingga menghasilkan lirik yang memiliki daya tarik dan makna yang khas. Lagu “Paralel” karya Febian Winanda memiliki nilai artistik dan simbolik yang tinggi, sehingga layak untuk dikaji secara akademis, khususnya melalui pendekatan semiotika. Penelitian ini bertujuan untuk mengidentifikasi makna dan pesan yang terkandung dalam lirik lagu “Paralel” sebagaimana dimaknai oleh para pendengarnya. Penelitian ini menggunakan Reception Theory dan teori budaya populer sebagai landasan teoretis. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan analisis semiotika Ferdinand de Saussure. Hasil penelitian menunjukkan bahwa mayoritas audiens berada pada posisi dominan, yaitu menerima pesan lagu sesuai dengan maksud penciptanya. Sementara itu, sebagian audiens berada pada posisi negosiasi, dengan menafsirkan makna lagu berdasarkan pengalaman pribadi masing-masing. Selain itu, setiap kata dan frasa dalam lagu tidak hanya dipahami secara literal, tetapi juga sebagai tanda (signifier) yang merujuk pada makna emosional atau simbolik (signified), seperti harapan, jarak, dan cinta tak berbalas. Relasi antara tanda dan makna bersifat arbitrer dan kontekstual, bergantung pada latar belakang sosial serta pengalaman pendengar.